Multiple influences of land transfer in the integration of Beijing-Tianjin-Hebei region in China. (July 2018) - Lu, Nachuan; Wei, Hejie; Fan, Weiguo; Xu, Zihan; Wang, Xuechao; Xing, Kaixiong; Dong, Xiaobin; Viglia, Silvio; Ulgiati, Sergio
Abstract: Land transfers are an important approach to Chinese farmland management and intensive crop production as well as a primary government strategy to promote Beijing-Tianjin-Hebei region development; these transfers are expected not only to generate social, economic, and ecological benefits but also to further Beijing-Tianjin-Hebei's regional development by means of more efficient and sustainable resource use. However, together with the challenges associated with this process, several contradictions and problems have arisen that are now critical political and social concerns. Therefore, a modern demonstration zone of sustainable agriculture in Yi County, Hebei Province, China, was selected as a case study for emergy-based performance and sustainability evaluation of the associated social, economic, and ecological benefits before and after land transfer. The results suggest that land transfers have induced fundamental changes to land use, which improved performance in terms of resource use and sustainability indicators (based on the emergy approach) and have produced ecological, economic, and social benefits mainly based on the increased link to the surrounding larger scale economic system via the increased demand for labor and services from outside. Therefore, the emergy results, while highlighting the achieved or potential benefits, also indicate that local improvements cannot be fully achieved if the entire supply chain of goods and resources is not suitably improved as well and that the local system is heavily affected by the larger-scale functioning of the economy as a whole, such that all links across scales need to be monitored and carefully addressed.